Bayesian D-optimal designs for error-in-variables models - Konstantinou, Maria; Dette, Holger (My University, 2017)
Copyright © 2017 John Wiley & Sons, Ltd. Bayesian optimality criteria provide a robust design strategy to parameter misspecification. We develop an approximate design theory for Bayesian D-optimality for nonlinear regression models with covariates subject to measurement errors. Both maximum likelihood and least squares estimation are studied, and explicit characterisations of the Bayesian D-optimal saturated designs for the Michaelis–Menten, Emax and exponential regression models are provided. Several data examples are considered for the case of no preference for specific parameter values, where Bayesian D-optimal saturated designs are calculated using the uniform prior and compared with several other designs, including the corresponding locally D-optimal designs, which are often used in practice. Copyright © 2017 John Wiley & Sons, Ltd.
Keywords: Bayesian optimal designs; classical errors; D-optimality; error-in-variables models